Peran Norma Deskriptif dan Kepribadian terhadap Perilaku Melawan Arah pada Pengendara Sepeda Motor - Aflah Zakinov Irta; Dewi Maulina; Guritnaningsih A. Santoso (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
This study aims to investigate the role of descriptive norms and personality traits in predicting contraflow riding behavior among motorcyclists. A correlational study was conducted to 156 riders who have the active riding licenses, aged 17 to 51 years old. Participants was given validated scenarios to measure descriptive norm and the contraflow riding behavior, and the Indonesian adapted version of the Big Five self-report to measure extraversion and conscientiousness traits. The results show that descriptive norms have a significant role in predicting contraflow riding behavior. Age has also a significant role in predicting contraflow riding behavior. When the riders perceived that many riders perform contraflow behavior and the younger their age, they are more likely to perform the contraflow riding behavior. Based on this study, the policy makers should make a serious effort in developing the descriptive norms to reduce contraflow riding behavior, especially among young motorcyclists.